Fast infrared variability from the black hole candidate MAXI J1535-571 and tight constraints on the modelling - Vincentelli FM; Casella P; Russell DM; Baglio MC; Veledina A; Maccarone T; Malzac J; Fender R; O'Brien K; Uttley P (OXFORD UNIV PRESS, 2022)
We present the results regarding the analysis of the fast X-ray/infrared (IR) variability of the black hole transient MAXI J1535-571. The data studied in thiswork consist of two strictly simultaneous observations performed with XMM-Newton (X-rays: 0.7-10 keV), VLT/HAWK-I (Ks band, 2.2 μm) andVLT/VISIR (M and PAH2_2 bands, 4.85 and 11.88 μm, respectively). The cross-correlation function between the X-ray and near-IR light curves shows a strong asymmetric anticorrelation dip at positive lags. We detect a near-IR QPO (2.5 σ) at 2.07 +/- 0.09 Hz simultaneously with an X-ray QPO at approximately the same frequency (f0 = 2.25 +/- 0.05). From the cross-spectral analysis, a lag consistent with zero was measured between the two oscillations. We also measure a significant correlation between the average near-IR and mid-IR fluxes during the second night, but find no correlation on short time-scales. We discuss these results in terms of the two main scenarios for fast IR variability (hot inflow and jet powered by internal shocks). In both cases, our preliminary modelling suggests the presence of a misalignment between the disc and jet.